Pilomotor seizures and status in non-paraneoplastic limbic encephalitis. - Wieser, S; Kelemen, A; Barsi, P; Vincent, A; Borbely, C; Rasonyi, G; Mueller, S; Hess, K; Wieser, H; Halasz, P (2005)
BACKGROUND AND AIMS: To describe an unusual clinical presentation of a patient with voltage-gated potassium channel Ab- positive, non-paraneoplastic limbic encephalitis. METHODS: We performed video-EEG monitoring, structural MRI, (18)F-FDG-PET, (1)H-MRS, neuropsychological testing and antibody serology. RESULTS: A 42-year-old male patient presented in an acute phase of non-paraneoplastic limbic encephalitis confirmed by MRI, with antibodies to voltage-gated potassium channels. His pilomotor status was pharmacoresistant to antiepileptic drugs, but responded to corticosteroid and azathioprine treatment. The MRI findings improved. The pilomotor seizures recurred when the immunosuppressive therapy was discontinued after 18 months. MRI at that time was consistent with hippocampal sclerosis. Complete seizure control was achieved after reintroduction of steroids. CONCLUSION: Pilomotor seizures were the predominant seizure type in this case of non-paraneoplastic limbic encephalitis. Immunosuppressive therapy may provide recovery including seizure control. However, long-term immunosuppression may be necessary to prevent relapse. Hippocampal sclerosis and chronic epilepsy might evolve as sequelae of limbic encephalitis.